Teste de marcha estacionária de seis minutos com uso de dispositivo de realidade virtual : uma alternativa ao teste de caminhada de seis minutos? - Sakaguchi, Camila Akemi (2016)
Introduction: The 6-minute walk test (6MWT) is one of the most frequently employed among the submaximal exercise capacity tests, with a limited use in clinical practice due to its requirement for a large physical space. Therefore, a virtual reality-assisted 6- Minute Stationary March Test (6MSMT-VR) is proposed as a modern and alternative tool for exercise capacity assessment in small-sized environments. Objectives: To compare and correlate physiological variables, energy expenditure (EE) and number of steps (NS) between the 6MWT and the 6MSMT-VR, using the first one as the standard. Methods: Apparently healthy subjects, aged 18 to 60 years old, were assessed by physical examination, spirometry, tested for physical activity level and later grouped as active (A) or non-active (NA). They, then, performed each test twice and answered a self-tailored satisfaction survey. Each result obtained was later compared and correlated. Results: In spite of the significant difference in NS between tests (p<0.001), a positive correlation (r=0.50) was found between them. A positive correlation was also found between the NS in the 6MSMT-VR and the total distance (TD) in the 6MWT (r=0.48) and for every other correlation value in the NA group. The EE, nevertheless, had a positive correlation value only for A group (r=0.40). No significant differences were obtained for hemodynamic variables and dyspnea, albeit the majority of patients (55%) reported greater Lower Limb Fatigue in the 6MSMT-VR. Conclusion: The 6MSMT-VR was well tolerated by the study’s population and may, thus, be considered an alternative to the 6MWT.